Improving cycling safety through infrastructure design: A bicycle simulator study. (March 2023) - Meuleners, Lynn; Fraser, Michelle; Roberts, Paul
Highlights: the development of safe cycling infrastructure is critical for increasing cycling in Australia, which will have significant health benefits for the community. increasing the bike lane width on curved sections of mid-block roads may benefit cyclists and their safety. the value of sharrows in a single lane roundabout is less clear. Unexpectedly, females rode further from the left curb when entering the roundabout, 'claiming the lane' more than males, irrespective of the presence of sharrows. Abstract: This study investigated the impact of two road treatments on cyclist behaviour using an bicycle simulator. The treatments were sharrows (presence or absence) at a roundabout and widening an on-road bike lane (width 1.2 m or 1.8 m) on a curved mid-block section of the road. Outcomes collected included count (e.g. number of lane excursions) and continuous responses (lane position upon entry into the roundabout, in metres from the curb). A convenience sample of 21 Perth-based participants was recruited between 1 July and 30 September 2021. The results found that the presence of sharrows was not significantly associated with the distance from the left curb when entering a single lane roundabout. However, females rode 0.44 m further from the left curb when entering the roundabout than males, which was significant (95 % CI = 0.02–0.85; p = 0.04). Riders, aged 26–40 years, also rode 0.61 m further from the left curb when entering the roundabout than riders aged 18–25 years, which was also significant (95 % CI = 0.18–1.05; p = 0.01). The rate of bike lane excursions significantly decreased by 68 % for the wide bike lane on the curved mid-block section of the road compared to the standard width bike lane (IRR = 0.32; 95 % CI = 0.11–0.88; p = 0.03). Riders, aged 26–40 years, had a significant increased rate of 8.72 excursions than riders aged 18–25 years (IRR = 8.72; 95 % CI = 3.32–22.89; p < 0.001). This study highlights that increasing the bike lane width on curved sections of mid-block roads may benefit cyclists. However, the value of sharrows in a single lane roundabout is less clear.